The Effect of Season on Semen Characteristics and Freezability in Bos indicus and Bos taurus Bulls in the Southeastern Region of Brazil - Koivisto, M. B. [UNESP]; Costa, M. T. A.; Perri, Silvia Helena Venturoli [UNESP]; Vicente, W. R. R. [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
The objectives of this study were to evaluate the effects of season in southeast of Brazil comparing genotypes on semen characteristics, freezability and peripheral plasma concentrations of testosterone. Ejaculates of five Bos indicus bulls and six Bos taurus bulls were evaluated over a period of 27 months, which was divided into winter (July, August, September), spring (October, November, December), summer (January, February, March) and autumn (April, May, June). Semen was evaluated according to standard procedures for ejaculate volume, sperm concentration, gross-motility, progressive motility and sperm morphology. After preparing and freezing the ejaculates according to commercial procedures, the straws were stored in liquid N(2) until post-thaw evaluation. Ejaculate volume, sperm concentration, gross-motility, progressive sperm motility, vigor and morphological sperm defects were significantly influenced by season and genotype (p < 0.05). Heat tolerance was better in B. indicus bulls than in B. taurus bulls characterized by lower values of sperm abnormalities throughout the observation period. The highest values were recorded for abnormal heads followed by cytoplasmatic droplets in B. taurus bulls. The proportion of ejaculates which were eliminated before freezing for reasons of bad quality was lower in the B. indicus bulls. Temporal changes in peripheral plasma testosterone concentrations were higher in B. indicus bulls than in B. taurus bulls not revealing seasonal influences. The results of this study show clear genotype differences regarding semen quality. Freezability of B. taurus semen varies considerably throughout the year, leading to a high proportion of eliminated ejaculates. Collecting semen from B. taurus bulls during the summer in an artificial insemination centre may not be profitable.